Criticisms of Current Financial and Trade Policies To Support Iranian Products in Selected Sectors - Ali Tousi; Ali Ghasemi; Hossein Dehghan Shourkand (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Trade and financial policies and instruments as a set of effective actions on the supply and demand of firms' products play a major role in stabilizing any economy and if gross domestic product, employment, imports and exports and inflation rate are considered as the most important macroeconomic variables, these instruments and policies will affect a significant portion of any economy. In this paper, it has been shown that the current trade and financial policies (in the last 20 years) have led to jobless growth. In addition, by using the latest statistical Input-Output table of I.R. of Iran, the impact of economic sanctions by reducing 30 percent of import of capital goods on key sectors has been calculated. Results show that in order to cope with sanction, if financial policies in key sectors change through 14.5 percent increase in banks' facilities and trade policies change through 9.3 increase in non-oil exports and 13.9 percent increase in imports of capital goods, more than 500.000 new jobs will be created and economic growth rate will increase more than 0.5 percent.